2011
DOI: 10.1007/s11071-011-0060-0
|View full text |Cite
|
Sign up to set email alerts
|

Four-wing hyperchaotic attractor generated from a new 4D system with one equilibrium and its fractional-order form

Abstract: In this paper, a new simple 4D smooth autonomous system is proposed, which illustrates two interesting rare phenomena: first, this system can generate a four-wing hyperchaotic and a four-wing chaotic attractor and second, this generation occurs under condition that the system has only one equilibrium point at the origin. The dynamic analysis approach in the paper involves time series, phase portraits, Lyapunov exponents, bifurcation diagram, and Poincaré maps, to investigate some basic dynamical behaviors of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Lately, Dadras et al [46] reported the following four-wing hyperchaotic system, which has only one unstable equilibrium…”
Section: Description Of the Switched Generalized Function Projective mentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, Dadras et al [46] reported the following four-wing hyperchaotic system, which has only one unstable equilibrium…”
Section: Description Of the Switched Generalized Function Projective mentioning
confidence: 99%
“…When a = 8, b = 40 and r = 14.9, and with the initial condition [10,1,10,1] T , system (5) is hyperchaotic and its attractor is shown in Figure 2. For more information on the dynamical behaviors of these two systems, please refer to [45,46].…”
Section: Description Of the Switched Generalized Function Projective mentioning
confidence: 99%
“…There has been an increasing amount of literature on hyperchaos [7,8]. Authors have introduced and studied different hyperchaotic systems such as switched hyperchaotic system [9], four-wing hyperchaotic attractor [10], hyperchaotic Chua's circuits [11], and hyperchaotic Lü attractor [12]. It is noted that there are countable numbers of equilibrium points in such reported hyperchaotic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Also, having more than one positive Lyapunov exponents is very important and to obtain them should be increased the system dimensions, but this can lead to instability, and thus, it is hard finding a chaotic system. Having more than one positive Lyapunov exponents causes the system to show very complex behaviors and very irregular responses [35]. Today, these systems are called hyper-chaotic systems with complex dynamical behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Having only one equilibrium point in a four-wing attractor almost impossible, but Dadras and Momeni [35] reported four-wing attractor which has only one equilibrium point that is interesting in itself. The research to find various types of multi-wing attractors has been done recently, so that Qi has introduced an eight-wing attractor with nine equilibrium points in 2012 [42].…”
Section: Introductionmentioning
confidence: 99%